(untitled) (IIUC Studies, 2021)
In the 10th Hijrah, the Prophet Muhammad (PBUH) performed Hajj (pilgrimage) only once in his life and delivered his historic ’Farewell Sermon’ for the liberation and welfare of the world humanity. This paper explores the importance and significance of the sermon in the context of its historical demand and its place in the world civilisation. The article also attempts to review historically on speaker, time and application of the speech to determine its place in perspective of world history and Islamic history as well. The methodology of the paper followed a qualitative approach comprised of the secondary source. It is argued that the sermon is the only historic speech in the world that incomparable provisions on liberation and welfare of humanity till the Final Day. The ultimate implication of the magnificent sermon is sustained ensuring its time was momentous and eventful; the more appropriate time cannot be estimated. Thus, according to historical analysis, the farewell sermon of the Final Apostle (PBUH) is the demand of time intimately and significantly that relevant to today’s life and society. IIUC Studies Vol.17, December 2020: 55-72